2016
DOI: 10.1097/md.0000000000004422
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative hepatitis B core antibody level is associated with inflammatory activity in treatment-naïve chronic hepatitis B patients

Abstract: Previous studies have shown that hepatitis B core antibody (anti-HBc) levels vary during different phases of disease in treatment-naïve chronic hepatitis B (CHB) patients and can be used as a predictor of both interferon-α and nucleoside analogue therapy response. However, there is no information on the association between the quantitative serum anti-HBc (qAnti-HBc) level and liver inflammation in CHB patients. Therefore, we investigated these relationships in a large cohort of treatment-naïve CHB patients. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 14 publications
2
35
0
Order By: Relevance
“…Moreover, the qAnti‐HBc level varies greatly at different phases of HBV infection . The qAnti‐HBc level was also reported to be significantly correlated with liver inflammation grade in treatment‐naïve CHB patients . At present, there is a lack data about the utility of qAnti‐HBc levels for diagnosis of significant inflammation in patients with normal or near‐normal ALT levels.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the qAnti‐HBc level varies greatly at different phases of HBV infection . The qAnti‐HBc level was also reported to be significantly correlated with liver inflammation grade in treatment‐naïve CHB patients . At present, there is a lack data about the utility of qAnti‐HBc levels for diagnosis of significant inflammation in patients with normal or near‐normal ALT levels.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that serum HBsAg of HBeAg-positive patients and serum HBV DNA of HBeAgnegative patients are valuable but not very satisfactory in predicting liver inflammation intensities and fibrosis levels [31][32][33][34][35][36]. Lately, preliminary studies have demonstrated that anti-HBc may be useful in predicting liver inflammation intensities and fibrosis levels [15][16][17][18][19][20]. is study indicated that the AUC of anti-HBc of HBeAg-positive patients in predicting pathological grades ≥G2 and ≥G3 was both close to that of serum HBsAg and both significantly greater than that of serum HBV DNA, and in predicting pathological stages ≥S2 and �S4 was both close to that of serum HBsAg and, respectively, significantly greater than and close to that of serum HBV DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies have explored the predictive value of anti-HBc for liver pathological states in patients with chronic HBV infection from a practical perspective, but the performance of this has not been investigated in detail [15][16][17][18][19][20]. To further characterize the theoretical and practical value of anti-HBc, we comparatively depicted the evolving patterns of anti-HBc versus serum HBsAg and HBV DNA following liver inflammation intensities and fibrosis levels and evaluated the performance of anti-HBc versus serum HBsAg and HBV DNA in predicting liver inflammation intensities and fibrosis levels in patients with chronic HBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Positive correlation between qAnti-HBc, transaminase levels and liver inflammation has been hypothesized by several authors. [ 24 25 26 ] Predictive value of pretreatment quantification of qAnti-HBc levels for the treatment response in CHB patients on Peg-IFN therapy has also been studied by Hou et al . [ 27 ] While the exact underlying mechanism of the positive correlation between serum qAnti-HBc level, serum alanine aminotransferase (ALT) level and inflammation severity remains to be examined, a possible mechanistic explanation for this association is that all of these features are determined by the host's immune responses.…”
Section: Discussionmentioning
confidence: 99%